The Apolipoprotein B/A1 Ratio is Associated With Metabolic Syndrome Components, Insulin Resistance, Androgen Hormones, and Liver Enzymes in Women With Polycystic Ovary Syndrome - He, Hui; Feng, Jiaxing; Zhang, Shike; Wang, Yu; Li, Jian; Gao, Jingshu; Cong, Jing; Gong, Yi; Wu, Xiaoke (Frontiers in Endocrinology, 2022)
Aim To evaluate the association between the apolipoprotein B/A1 ratio (ApoB/ApoA1) and metabolic and endocrine parameters in women with polycystic ovary syndrome (PCOS). Methods This study was a secondary analysis of the Acupuncture and Clomiphene for Chinese Women with Polycystic Ovary Syndrome trial (PCOSAct), and 957 subjects with available ApoB and ApoA1 measurements were included. Tests for linear trends and linear regression were used to assess the relation between the ApoB/ApoA1 ratio and metabolic and endocrine parameters. Logistic regression was used to estimate the association between the ratio and risk of metabolic syndrome (MetS) and insulin resistance (IR). The receiver operating characteristics (ROC) curve was used to determine the predictive value of the ApoB/ApoA1 ratio for MetS and IR. Results The results showed that the ApoB/ApoA1 ratio was positively associated with waist circumference, systolic blood pressure, total cholesterol, triglycerides, low-density lipoprotein, fasting plasma glucose, fasting insulin, homeostatic model assessment-insulin resistance, high free testosterone, high free androgen index, alanine transferase, aspartate transferase, and higher prevalence of MetS and IR, but was negatively correlated with high-density lipoprotein and sex hormone-binding globulin after adjusting for age and body mass index. Logistic regression showed that compared with the ApoB/ApoA1 ratio in first quartile, those in the fourth quartile demonstrated a higher risk of MetS (OR: 24.48, 95%CI: 8.54–70.15, P trend <0.001) and IR (OR: 1.78, 95%CI: 1.10–2.87, P trend <0.05) after adjusting for confounding factors. ROC curve results showed that the AUCMetS was 0.84 (95%CI: 0.81–0.86) and had 86.8% sensitivity and 70.3% specificity with a threshold value of 0.64, and the AUCIR was 0.68 (95%CI: 0.64–0.71) and had 74.3% sensitivity and 58.2% specificity with a threshold value of 0.56. Conclusions Increased ApoB/ApoA1 ratio was associated with worse MetS components, IR, and elevated androgen hormones and liver enzymes. The ratio might be a useful tool to screen for MetS and IR in PCOS patients.